Evolution of antimicrobial resistance and serotype distribution of Streptococcus pneumoniae isolated from children with invasive and noninvasive pneumococcal diseases in Algeria from 2005 to 2012. (July 2015) - Ramdani-Bouguessa, N.; Ziane, H.; Bekhoucha, S.; Guechi, Z.; Azzam, A.; Touati, D.; Naim, M.; Azrou, S.; Hamidi, M.; Mertani, A.; Laraba, A.; Annane, T.; et al.
Abstract: Pneumococcal infections are a major cause of morbidity and mortality in developing countries. The introduction of pneumococcal conjugate vaccines (PCVs) has dramatically reduced the incidence of pneumococcal diseases. PCVs are not currently being used in Algeria. We conducted a prospective study from 2005 to 2012 in Algeria to determine antimicrobial drug resistance and serotype distribution of Streptococcus pneumoniae from children with pneumococcal disease. Among 270 isolated strains from children, 97 (36%) were invasive disease; of these, 48% were not susceptible to penicillin and 53% not susceptible to erythromycin. A high rate of antimicrobial nonsusceptibility was observed in strains isolated from children with meningitis. The serotype distribution from pneumococci isolated from children with invasive infections was (by order of prevalence): 14, 1, 19F, 19A, 6B, 5, 3, 6A and 23F. Multidrug resistance was observed in serotypes 14, 19F, 19A and 6B. The vaccine coverage of serotypes isolated from children aged <5 years was 55.3% for PCV7, 71.1% for PCV10 and 86.8% for PCV13. Our results highlight the burden of pneumococcal disease in Algeria and the increasing S. pneumoniae antibiotic resistance. The current pneumococcal vaccines cover a high percentage of the circulating strains. Therefore, vaccination would reduce the incidence of pneumococcal disease in Algeria.